FOAMING CHARACTERISTICS OF THE FOOD-INDUSTRY BIOLOGICAL WASTEWATER TREATMENT PLANT - Manyele, S. V. (Tanzania Journal of Engineering and Technology, 2018)
Intensive foaming observed during aeration of the aerobic food industry wastewater treatment plant is presented. This study was conducted to establish the foaming characteristics using a pilot three-phase fluidized bed bioreactor (TPFBB). A fluidization column (0.2 m i.d. and 6 m high) was used. The TPFBB was loaded with variable masses of novel biomass support particles (BSP). Wastewater samples collected from a plant processing both vegetable oil (VOPWW) and soap (SPWW) were immediately introduced in the TPFBB for aeration. The characteristics studied include: variation of foam volume with time, foam multiplicity, foaming and foam collapse rates. The SPWW produced excessive foam volumes at a higher rate and higher foam multiplicity compared to VOPWW. Dilution, increasing aeration rate or BSP loading led to higher foaming rate, which decreased with time. Spraying wastewater at the top of the liquid surface minimized foaming rate.